Synthesis and evaluation of chromone-2-carboxamido-alkylamines as potent acetylcholinesterase inhibitors - Suwanhom, Paptawan; Nualnoi, Teerapat; Khongkow, Pasarat; Lee, Vannajan Sanghiran; Lomlim, Luelak (Springer Verlag, 2020)
Alzheimer’s disease (AD) is considered one of the greatest global public burdens. Pathophysiology of AD is proposed to be associated with reduced levels of the neurotransmitter acetylcholine (ACh). Cholinesterase enzymes, namely acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) cleave ACh via hydrolysis. Cholinesterase inhibitors (ChEIs) are the main group of drugs currently used for the treatment of AD. Novel chromone-2-carboxamido-alkylamines (7–18) were designed, synthesized, and evaluated for cholinesterase inhibitory activity. The compounds exhibited potent AChE inhibitory activities at micromolar range (IC50 0.09–9.16 µM) and demonstrated weak BChE inhibitory activities (IC50 12.09–44.56 µM). Compound 14 (IC50 0.09 ± 0.02 µM) was the most potent AChEI in this series; it showed higher activity than the clinical used drug tacrine. Enzyme kinetic study suggested that 14 was an uncompetitive inhibitor. Molecular docking study revealed that 14 was a dual-binding site inhibitor. Compound 14 did not induce any concentration-related cytotoxic effect against SH-SY5Y cells. It also showed neuroprotective effect in the cell line. Chromone-2-carboxamido-alkylamines can be promising lead compounds for development of anti-Alzheimer’s agents. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.